AN ANALYSIS OF THE FUNCTIONING OF TRANSFERS BETWEEN THE STATE BUDGET OF UKRAINE AND LOCAL BUDGETS IN 2015—2018 - Пухир, Світлана; Данилевич, Христина (Socio-economic relations in the digital society, 2019)
The article it is noted that budget decentralization is one of the basic preconditions for the independent and effective activity of local authorities in the management of the territory, the ability to provide high quality andaff ordable services to the population. Th e presence of signifi cant volumes of intergovernmental transfers testifies to the presence of unresolved problems in the modern system of intergovernmental fi scal relations. Analyzes the functioning of intergovernmental transfers in the context of the implementation of decentralization of power and budgetary decentralization reforms. Th e high centralization of budget resources is determined. The effectiveness of transfer of part of delegated authority to local authorities and increase of tax revenues to local budgets are highlighted. It is noted that the real autonomy of local budgets is not achieved. Th e features of the structure of local budget revenues are revealed. The largest fiscal significance belongs to the personal income tax. Signifi cant dependence of local budgets on transfers from the state budget is established. The system of horizontal alignment of local budgets’ fiscal capacity does not reduce the signifi cant diff erences in the revenue capacity of local budgets. The alignment mechanism isimperfect and requires the introduction of a median-based mechanism that will ensure a real balance of local budgets. The imperfection and incompleteness of normative-legal provision of management of intergovernmental transfers are established. There is no clear and mutually exclusive list of own and delegated bodies of executive power to local self-government authorities in the branches of the budget sphere. There is no diff erentiation of expenditures for the fulfillment of the powers of local self-government bodies and their delegated state. The article substantiates the need for further reform of transfers between the state budget and local budgets of Ukraine.
Keywords: intergovernmental transfers; subsidies; subventions; local budgets; fiscal capacity; horizontal alignment.; own and delegated powers